Ketidakadilan Gender dan Kritik Sosial dalam Laapataa Ladies: Pendekatan Feminisme dalam Analisis Film - Machfud, Nailul Ulah Al Chumairoh (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study analyzes the film Laapataa Ladies through a feminist approach to uncover the gender inequalities and social critique embedded in its narrative. As a representation of patriarchal Indian society, the film explores various dimensions of gender injustice, including gender-based social expectations, unequal power relations, and restrictive social norms that control women's freedom. Using Judith Butler's theory of gender performativity, this study demonstrates that gender roles in the film are constructed through the repetition of social norms that position women in subordinate roles. The film also reveals how socioeconomic inequality reinforces patriarchal dominance, as women from lower economic classes face economic pressures that limit their life choices. Additionally, the study highlights the role of women in perpetuating patriarchy through the internalization of traditional values, as illustrated in the interactions between mothers-in-law and their daughters-in-law. Through humor and satire, Laapataa Ladies deconstructs dominant patriarchal narratives and highlights spaces for women's resistance against restrictive norms. The main female characters serve as symbols of defiance against an oppressive system, even within a context fraught with risks. This study concludes that Laapataa Ladies not only reflects gender inequality in Indian society but also functions as a social critique that encourages discourse for change toward a more inclusive and equitable society.